SOCIAL RESPONSIBILITY OF ACADEMIC COMMUNITY: A CASE STUDY FROM KERALA - Mariya T Cheeran (nternational Journal of Advanced Research in Management and Social Sciences, 2015)
Free Drug Cell working in the Government Hospital, Ernakulum is initiated and operated by the Department of Social Work, Rajagiri college of Social Sciences, Ernakulum, Kerala. More than one lakh people are benefitting from this cell every year. The author was the coordinator of this departmental activity. This paper explains the operations and objectives of the free drug cell. This paper may act as baseline document for similar initiatives across globe, especially in developing and undeveloped countries